THE IMPACT OF ORGANIZATIONAL LEARNING MECHANISMS ON THE QUALITY OF ORGANIZATIONAL PERFORMANCE (World Economics and Finance Bulletin, 2026)
The study of organizational learning has been growing in recent years because it is seen as enabling organizations to improve performance in rapidly changing environments. This study aimed to determine the impact of organizational learning mechanisms on organizational performance quality. The study investigates four organizational learning mechanisms, including individual learning, group learning, knowledge management with continuous learning culture and their effect on organizational performance, which is multidimensional. In order to conduct this study, a descriptive analytical design was employed in which a structured questionnaire was developed based on approved scales used widely in the literature of organizational learning and performance and was applied to respondents who were managers, supervisors and managerial leaders working in different management levels of selected organizations. 385 questionnaires were distributed, out of which 358 were returned. After verifying the completeness and consistency of the answers, 342 questionnaires were used for statistical analysis, yielding a response validity rate of 97.7%. The questionnaire measures organizational performance quality through four basic dimensions: operational efficiency, organizational effectiveness, innovation capability and stakeholder satisfaction. The results of the study using multiple linear regression showed that the organizational learning mechanism has a strong, significant impact on institutional performance quality (R2 = .731, F = 102.47, p < 0.001). The study is useful as it provides statistical evidence of the integrated impact of organizational learning mechanisms. This study will help managers in enhancing organizational performance by implementing organizational learning
Keywords: organizational learning; learning mechanisms; quality of institutional performance